2006
DOI: 10.1093/toxsci/kfm001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Exposure to Perchlorate on Thyroid and Reproductive Function in Zebrafish

Abstract: The objectives of this study were to determine the effects of prolonged exposure to perchlorate on (1) thyroid status and reproductive performance of adult zebrafish (Danio rerio) and (2) F1 embryo survival and early larval development. Using a static-renewal procedure, mixed sex populations of adult zebrafish were exposed to 0, 10, and 100 mg/l nominal concentrations of waterborne perchlorate for 10 weeks. Thyroid histology was qualitatively assessed, and females and males were separated and further exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 34 publications
6
50
1
Order By: Relevance
“…Previous work in frogs and birds has shown that females do transfer BDE-47 to their eggs (Liu et al, 2011;Verreault et al, 2006), and thus the offspring in this study were likely exposed. Our major finding was that the average mass of neonates tended to be larger in the BDE-47 treated animals, which is similar to findings in zebrafish exposed to the thyroid disruptor perchlorate during development (Mukhi and Patiño, 2007). Yet a study also conducted in zebrafish exposure during development to BDE-47 found that high concentrations yielded smaller individuals (Lema et al, 2008).…”
Section: Neonatessupporting
confidence: 82%
“…Previous work in frogs and birds has shown that females do transfer BDE-47 to their eggs (Liu et al, 2011;Verreault et al, 2006), and thus the offspring in this study were likely exposed. Our major finding was that the average mass of neonates tended to be larger in the BDE-47 treated animals, which is similar to findings in zebrafish exposed to the thyroid disruptor perchlorate during development (Mukhi and Patiño, 2007). Yet a study also conducted in zebrafish exposure during development to BDE-47 found that high concentrations yielded smaller individuals (Lema et al, 2008).…”
Section: Neonatessupporting
confidence: 82%
“…PCP decreased the plasma T4 levels in rats (BruckerDavis, 1998;Kawaguchi et al, 2008). Decreased T4 levels are frequently observed in mammals, amphibian and fish models exposed to TH endocrine disruptors, e.g., PBDEs (Tomy et al, 2004;Ellis-Hutchings et al, 2006;Lema et al, 2008;Yu et al, 2010), PCBs (Donahue et al, 2004;Martin and Klaassen, 2010;Schnitzler et al, 2011), and perchlorates (Mukhi and Patino, 2007;Opitz et al, 2009;Schmidt et al, 2012). Decreased TT4 and increased TT3 levels and the consequent increased ratio of T3/T4 are frequently observed in fish exposed to TH endocrine disruptors (Chen et al, 2012;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that if such processes are disturbed by endocrine disrupting compounds, this could have a dramatic impact on the thyroid endocrine system and reproduction (Mukhi and Patino, 2007). The development of bioassays that measure changes in gene expression provide molecular strategies and increase mechanistic understanding of thyroid disruptive effects on development and homeostasis (Zhang et al, 2006;Veldhoen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%